2000
DOI: 10.1016/s0165-2427(00)00226-9
|View full text |Cite
|
Sign up to set email alerts
|

The acute phase response of haptoglobin and serum amyloid A (SAA) in cattle undergoing experimental infection with bovine respiratory syncytial virus

Abstract: The ability of a pure virus infection to induce an acute phase protein response is of interest as viral infections are normally considered to be less efficient in inducing an acute phase protein response than bacterial infections. This was studied in a bovine model for infection with bovine respiratory syncytial virus (BRSV), analysing the induction of the two most dominant bovine acute phase proteins haptoglobin and serum amyloid A (SAA). Strong and reproducible acute phase responses were detected for both pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
164
3
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(190 citation statements)
references
References 25 publications
18
164
3
5
Order By: Relevance
“…Hp is the most sensitive marker of inflammation in cows [2,7,8]. Since most of the cows suffering from amyloidosis examined in the present study showed increases in both SAA and Hp levels, it was thought that the increase in SAA level was mainly caused by concomitant inflammation.…”
mentioning
confidence: 57%
“…Hp is the most sensitive marker of inflammation in cows [2,7,8]. Since most of the cows suffering from amyloidosis examined in the present study showed increases in both SAA and Hp levels, it was thought that the increase in SAA level was mainly caused by concomitant inflammation.…”
mentioning
confidence: 57%
“…In the clinical field, APPs may serve as indicators of prognosis and the effects of treatment. The magnitude and duration of the acute phase response reflects the severity of the infection and underlying tissue damage (Heegaard et al 2000).…”
Section: The Diagnostic Utility Of Acute Phase Proteins In Veterinarymentioning
confidence: 99%
“…Veterinary Biomarker Discovery: Proteomic Analysis of Acute Phase Proteins 191 2.1 Modulation of acute phase proteins during disease in swine Alteration in APP expression has been associated with a number of food animal diseases (Table 1), including mastitis, metritis, and amyloidosis in lactating dairy cattle (Chan et al, 2010;Safi et al, 2009;Suojala et al, 2008;Eckersall et al, 2001Eckersall et al, , 2006Takahashi et al, 2006;Grönlund et al, 2003Grönlund et al, , 2005; sepsis, trauma, and respiratory diseases in swine (Amory et al, 2007;Sorensen et al, 2006;Hultén et al, 2003;Heegaard et al, 1998;Eckersall et al, 1996); infectious bronchitis virus in chickens (Nazifi et al, 2011); respiratory diseases in beef cattle (Orro et al, 2011;Heegaard et al, 2000;Godson et al, 1996;Horadagoda et al, 1995); as well as pulmonary damage and caseous lymphadenitis in sheep (Eckersall et al, 2007;Pfeffer and Rogers, 1989 In swine, increased levels of serum HPT have been associated with pathological indications of Mycoplasma hyopneumoniae, a leading cause of porcine enzootic pneumonia (Amory et al, 2007). Similarly, serum concentrations of HPT and SAA were elevated in pigs with experimentally induced Actinobacillus pleuropneumoniae pneumonia Heegaard et al, 1998).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Conversely, there have been several investigations into the acute phase response during both naturally-occurring and experimentally-induced bovine diseases. In studies of bovine respiratory disease, peak levels of serum SAA and HPT were reported during week 3 of an outbreak of respiratory disease in calves caused by respiratory syncytial virus (Orro et al, 2011), while experimental infection with respiratory syncytial virus caused maximal increases in serum levels of HPT and SAA in cattle as early as 7-8 days following inoculation (Heegaard et al 2000). Of the bovine diseases studied, however, APP expression has been investigated most extensively during mastitis in lactating dairy animals (Safi et al, 2009;Suojala et al, 2008;Eckersall et al, 2006Eckersall et al, , 2001Grönlund et al, 2003;Hirvonen et al, 1999).…”
Section: Modulation Of Acute Phase Proteins During Ruminant Diseasementioning
confidence: 99%